Principles of public service: system-activity dimension - Shovkun, Yu. I. (Вісник Харківського національного університету внутрішніх справ, 2024)
A system of principles of public service has been formed, which consists of three principle blocks. International principles of public service: supremacy of law; legality; effectiveness; objectivity; impartiality; justice; virtue; public activity regarding the management of state affairs, in particular those related to entry into public service, its completion and legislative support; balance of public and private interests when making decisions; transparency (passing public service and activities of public servants); responsibility of public servants to the population and the state for their professional activities; publicity, which involves the mandatory publication of open information about the work of public servants, etc. Principles of public administration: a) organizational; b) functional; c) targeted; d) accommodative. Legal principles: a) general principles of law (humanism, democracy, separation of powers into legislative, executive and judicial, legal certainty, presumption of innocence, proportionality, equality, legal responsibility; b) principles of administrative law (openness and transparency, flexibility, compliance human rights and freedoms, efficiency, prohibition of arbitrariness, innovation, competence, accountability and control, priority of laws of Ukraine and international documents regulating administrative and legal relations, social cohesion, stability and long-term orientation); c) special principles of law that regulate the passage of service by certain categories of public servants (equal access to public service, choice, patriotism, people's power, loyalty to constitutional duty and oath in case of taking it, state support, observance of official (executive) discipline and professional ethics, independence, failure to comply with illegal orders and instructions, consolidation of state and local interests, readiness for prompt performance of official tasks).